Significance of Ramped Temperature in the Dynamics of Unsteady Viscoelastic Fluid Subjected to Lorentz Force - Khan, Ilyas (Frontiers in Physics, 2022)
Viscoelastic fluids are almost everywhere and very useful in the industry such as polymers, paints, DNA suspensions, etc. This article aims to study the significance of ramped temperature on the dynamics of viscoelastic fluid. Magnetohydrodynamic (MHD) effect is considered in the presence of Lorentz force. The flow is considered in a porous medium using generalized Darcy’s law. Heat transfers through convection and the fluid near the plate takes heat in a ramped nature. Instead of the classical fluid model which has certain limitations, a generalized model is considered with fractional derivatives of Atangana-Baleanu type. The well-known technique of Laplace transform was adopted to obtain the solutions which are displayed in various plots with detailed discussion analysis. From the graphical analysis, it is worth noting that the Atangana-Baleanu fractional model shows a good memory effect on the dynamics of the viscoelastic fluid as compared to its classical form.